1993
DOI: 10.1302/0301-620x.75b3.8496209
|View full text |Cite
|
Sign up to set email alerts
|

Vertebral artery injury during anterior decompression of the cervical spine. A retrospective review of ten patients

Abstract: Ten patients who suffered iatrogenic injury to a vertebral artery during anterior cervical decompression were reviewed to assess the mechanisms of injury, their operative management, and the subsequent outcome. All had been undergoing a partial vertebral body resection for spondylitic radiculopathy or myelopathy (4), tumour (2), ossification of the posterior longitudinal ligament (1), nonunion of a fracture (2), or osteomyelitis (1). The use of an air drill had been responsible for most injuries. The final con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
118
0
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 214 publications
(123 citation statements)
references
References 18 publications
1
118
0
4
Order By: Relevance
“…Moreover, due to erosion of the anatomical structures, bony landmarks are not always reliable. Especially when the vertebral artery runs an abnormal course, screw placement has a potential risk of neurovascular injury, and vertebral artery injury on the dominant side can cause cerebellar infarction and possibly fetal sequelae [2,22,23]. Moreover, due to severe spinal deformity and small anatomical size of the vertebra (the lateral mass and pedicle) in the most RA cervical lesions, screw placement procedures are highly technically demanding and pose the potential risk of neurovascular injuries even though intraoperative fluoroscopy is used.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, due to erosion of the anatomical structures, bony landmarks are not always reliable. Especially when the vertebral artery runs an abnormal course, screw placement has a potential risk of neurovascular injury, and vertebral artery injury on the dominant side can cause cerebellar infarction and possibly fetal sequelae [2,22,23]. Moreover, due to severe spinal deformity and small anatomical size of the vertebra (the lateral mass and pedicle) in the most RA cervical lesions, screw placement procedures are highly technically demanding and pose the potential risk of neurovascular injuries even though intraoperative fluoroscopy is used.…”
Section: Discussionmentioning
confidence: 99%
“…VA injury is a rare but profound complication of ACSO [2,17,25,35]. The reports included in this study presented several mechanisms or risk factors of VA injury in ACSO.…”
Section: Causesmentioning
confidence: 97%
“…Unrecognized VA tortuosity or other anomalies, such as a VA located anterior to the transverse process, may also result in intraoperative injury [4,15,17,39]. The presence of a softened lateral cortex due to tumor or infection has been implicated in VA injury during operation [4,5,19,35]. In addition, a VA weakened by radiation or infection is also at risk for injury [5,19].…”
Section: Causesmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of iatrogenic VA injury in anterior cervical decompression procedures has been reported to range from 0.18 to 2.78 % [1,[19][20][21][22]. James et al [19] reported that VA injury can occur if decompression is asymmetric or overly aggressive.…”
Section: Discussionmentioning
confidence: 99%